Animation-Based Interactive Media Education on Reducing Personal Hygiene Performance (PHP) Scores in Adolescents - Melani Agis Marludia; Rifa Fauziah Syaifia Putri; Vera Dumonda Silitonga; Fernando Sam Yunior; Widi Nurwanti (Journal Center of Excellent : Health Assistive Technology, 2023)
Dental oral health according to WHO (2012) is a condition of the oral cavity including teeth that are free from throat cancer, tooth decay, infections and wounds in the mouth, tooth loss, and other diseases that can limit individuals from chewing, biting, speaking, smiling and the psychosocial well-being of the individual. Increasing the degree of dental and oral health does not escape the provision of interesting dental and oral health counseling, one of which is animation-based interactive media. The purpose: to determine the effectiveness of animation-based interactive media on increasing knowledge, brushing teeth skills, and decreasing personal hygiene performance (PHP) scores in adolescents. Research Methods: This study uses a survey method with a pre-post design approach. The survey will be conducted on 32 adolescent respondents with the types of questionnaires, namely questionnaires, check list sheets and PHP examination sheets. Results: There was an increase in previous knowledge on a score of 50% for moderate criteria, 12.5% ??bad, 37.% good, experiencing an increase in the post test to 100% for good criteria. An increase also occurred in the act of brushing teeth with pre test score 93,75% of bad criteria, 6,25% of moderate criteria, that score change became 100% with good criteria. Scores of personal hygiene performance (PHP) also change with pre test scores 78,125% of moderate and 21,875% with bad criteria. That both scores change became 37,5% with very good crietria and 62,5% with good criteria.  Conclusion: there is an effect of animation-based interactive media on increasing knowledge, brushing teeth skills and decreasing personal hygiene performance (PHP) scores in adolescents at SMAN 72 Jakarta.